Injectable ion-coordinated double-network conductive hydrogel for spinal cord injury repair - Yu, Huan; Liu, Fan; Hu, Yaorui; Wan, Weikang; Liu, Qing; Zhou, Shuai; Zhang, Luping; Li, Liming; Huang, Fei (Frontiers in Bioengineering and Biotechnology, 2025)
The mammalian central nervous system (CNS) demonstrates a severely limited capacity for spontaneous neural regeneration after traumatic spinal cord injury (SCI). Structural repair is also highly constrained due to the inhibitory microenvironment. This inherent limitation persists throughout the recovery phase and often leads to severe motor and sensory dysfunction, profoundly impairing patients’ quality of life. Current clinical treatments, including surgical decompression, pharmacological interventions, and rehabilitation therapy, can only partially relieve symptoms. They are not enough to promote neural regeneration and functional recovery. There is an urgent need to develop novel therapeutic approaches to overcome this challenge. This study developed and created an injectable double-network conductive hydrogel, it coordinates iron ions (Fe3+) using dynamic Schiff base bonds and metal ion coordination. The conductive hydrogel aids in spinal cord injury repair through various mechanisms, such as reducing glial scar formation, promoting remyelination, and providing neuroprotection. This makes it an injection therapy with promising prospects for clinical translation in the field of nerve regeneration.